KONTRIBUSI DAYA LEDAK OTOT TUNGKAI DAN DAYA LEDAK OTOT LENGAN TERHADAP KEMAMPUAN TOLAK PELURU TEKNIK O’BREIN - Ali Mardius; Yuni Astuti; Kibadra Kibadra (Universitas Pahlawan Tuanku Tambusai, 2019)
The study aims to determine the contribustion of explosive power arm and leg muscles personal or groups with the ability the O’brein technique ini shot put.The research was a guantitative method using corelational research design. The population was athlete track and field UKO University Bung Hatta as much as 40 athlete. Was taken by purposive random sampling as much as 30 athlete. The instrument standing broad jump was used to measure leg muscles explosive power. The instrument medicine ball put tes was used to measure arm muscles explosive power and skil of the technique o’brain was used to measure shot put.The result empirically showed that: 1) the contribution of leg muscle explosive power of the shot put capability was 14,36% 2) the contribution of the explosive power of the arm muscles shot put athlete track and field ability was 19,18%. 3) the contribution of leg and arm muscle explosive power joinly to word o’brain technique short put was 25,70%.